Toxin Profiling of Amanita citrina and A. sinocitrina: First Report of Buiotenine Detection - Yi-Zhe Zhang; Yi Yao; Kai-Ping Zhang; Jia-Qi Liang; Jia-Ju Zhong; Zhong-Feng Li; Hai-Jiao Li; Fei Xu (Toxins)
Amanita species are widely distributed worldwide. Many of these species are poisonous and can cause health problems, resulting in morbidity and mortality. The toxins responsible for poisoning are amatoxins, aminohexadienoic acid, ibotenic acid, muscimol and muscarines, which damage the liver, kidney, central nervous system and parasympathetic nervous system. In recent years, several toxins have been discovered from different poisonous mushrooms. In this study, multiwalled carbon nanotube purification and ultrahigh-performance liquid chromatography–tandem mass spectrometry (UPLC-MS/MS) was used for the sensitive detection and targeted quantitative screening of 12 mushroom toxins (muscarine, two isoxazole derivatives, three tryptamine alkaloids, three amatoxins and three phallotoxins) from Amanita citrina, A. citrina var. grisea and A. sinocitrina. This study found that buiotenine, one of the tryptamine alkaloids, was detected in A. citrina and A. sinocitrina with an average content of 2.90 and 1.19–6.70 g/kg (n = 3) in the dried mushrooms, respectively. None of the 12 common toxins were discovered in A. citrina var. grisea. These results provide reference data for future research on the role of toxins in the evolution of Amanita mushrooms. Future studies should explore the biosynthetic pathways and ecological roles of these toxins in Amanita species.